TRANSFORMASI ORGANISASI UNIT KERJA PENGADAAN BARANG DAN JASA PEMERINTAH DAERAH KABUPATEN BUTON TENGAH - Indrawan, La Ode Syarif; Islamy, La Ode Syaiful; Abidin, Zainul (Governance, 2025)
Organizational transformation is a form of change to encourage organizations to be able to adapt to public demands and organizational needs. Organizational transformation goes through three stages, namely unfreezing, changing, and refreezing. The purpose of the research is to explain the organizational transformation process of the Goods and Services Procurement Work Unit of the Central Buton Regency in realizing transparency. The research method is qualitative descriptive with three data collection methods, namely interviews, observations, and documentation. The results of the study show that the introduction stage of organizational transformation is carried out through the introduction process, both organizational structure, human resource recruitment and employee work management. Furthermore, the stage of organizational change of UKPBJ in Central Buton district is carried out with a gradual process, so that its implementation has encouraged the procurement of goods and services that are accountable, transparent and responsive. Furthermore, this Refreezing Stage  aims to strengthen and accept the changes that have been made so that they become new habits and are embedded in the organizational culture. In general, it can be concluded that organizational transformation encourages good organizational governance and the success of transformation is greatly influenced by the commitment of leaders in the regions.